Location-based data access control scheme for Internet of Vehicles. (September 2020) - Jiang, Mei; Wang, Hao; Zhang, Wenying; Qin, Hong; Sun, Xi
Abstract: Internet of Vehicles (IoV) is a typical representative of the Internet of Things in the area of transportation systems. Due to the mobility of vehicles, most applications for IoV are based on the location information. How to provide location-based access control is especially important for the IoV environment. Based on the multi-authority attribute-based encryption, we propose a novel location-based encryption scheme that enables both attribute-based and location-based access control for cloud storage. In this scene, vehicles can access data only if they arrive at a designated location and their attributes satisfy the access policy simultaneously. In the deployment of our scheme, we introduce fog computing and blockchain technologies. We deploy the fog nodes in the data access area to issue location-based keys and aid decrypting for vehicles, while we deploy the blockchain system to publish public parameters. The experiment shows that our scheme is feasible in practical applications.